Assessing the development of transport and logistics sector in Azerbaijan and the impact of transport investment: cross-country analysis - Mehriban Samadova; Nazira Huseynova; Aliya Hajigayibova (Problems and Perspectives in Management)
The study aims to analyze the transport and logistics sector development in Azerbaijan compared with International Transport Forum (ITF) countries and assess investment impact on it. The research base consists of OECD and World Bank data for the sample of 41 ITF countries for 2010–2022 regarding 19 indicators that characterize the level of transport and logistics sector’s development, investment, and maintenance spending. Based on Ward’s clustering, Sturges rule, and normalization, sample countries were divided into six clusters depending on the transport and logistics sector development in 2010, 2015, and 2022 (using STATA and Statgraphics Centurion). In 2022, Azerbaijan remained part of Cluster 1 (mostly European countries), just as in 2015 and 2010. Pearson correlations were applied to prove the relationships between 19 indicators in this field. Arellano–Bond dynamic panel-data estimation was made for Cluster 1, including Azerbaijan (32 countries for 2010–2022). Based on the constructed dynamic regression models for panel data, it was confirmed that with every 1% increase in road/rail investment, the length of roads/rail tracks/electrified rail tracks will increase by 0.03% with 2-year lag, 0.03% with a 1-year lag, and 0.06% with a 1-year lag. A 1% increase in value added by machinery and transport equipment will lead to a 0.03% increase in the length of electrified rail tracks with 2-year lag and an increase in rail investment by an average of 0.1% without lag.